Synthesis of Novel PCMX Derivative (International Journal of Scientific Research in Science and Technology, 2024)
Chloroxylenol, or parachlorometaxylenol (PCMX), is an antiseptic and disinfectant agent used for skin disinfection and surgical instruments. It is found in antibacterial soaps, wound-cleansing applications, and household antiseptics. Their analogues viz. hybrid / ester molecules also possess various biological activities which prompted us to synthesize a novel analogue for their future application as bioactive molecule. The synthesized compound was unambiguously characterized by IR, 1HNMR, elemental analysis and mass spectral data.